Premium Private Label strategies: Social networks and traditional perspectives - Eloy Gil-Cordero; Francisco Javier Rondan-Catalu\~na; Manuel Rey-Moreno (Journal of Innovation & Knowledge (JIK), 2021)
The main aim of this work is to analyze Premium Private Labels (PPL) in the food sector. To do so, we have obtained data from both on-line and off-line channels, analyzing social networks, specifically Twitter, and from carrying out personal surveys of customers in the sales point to check their opinions about the perceived quality, brand value, and other PPL-related variables. We analyzed a total of 7 Twitter accounts of the main supermarket and hypermarket chains over a year and did 600 customer surveys in points of sale. Among the main results stands out the fact that the perceived quality of the PPL compared with the brand leader varies among the main distributors. There are also significant differences between the brand value of the 3PPL analyzed. On the other hand, no relation was detected between the income levels and the brand equity of PPL buyers.
Keywords: M31; M19; 650; perceived value; Premium Private Labels; retailing; social network sites